KESESUAIAN HASIL UJI CBR LAPANGAN TERHADAP PERKERASAN JALAN BETON PERUMAHAN GRIYA CURUP EMBUN KOTA PAGAR ALAM - Erwin Eka Putra; Kiagus Muhammad Aminuddin; Arie Putra Usman; Akhirini Akhirini; Hendrik Jimmyanto (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2026)
This study aims to assess the alignment of field California Bearing Ratio (CBR) test results with the design specifications for concrete pavement in the construction of Public Infrastructure, Facilities, and Utilities (PSU) for Low-Income Housing (MBR) in Griya Curup Embun Housing Phases I and II, Pagar Alam City. CBR testing was conducted on seven road segments, evaluating both the subgrade and granular (sirtu) layers using the field CBR method as per SNI 1738:2011 . The results indicate that all segments met the technical requirements, with CBR values exceeding the minimum standards greater than 6% for subgrade soil and greater than 60% for granular layers as stipulated in Circular Letter No. 110/KPTS/Dr/2022. One segment (Segment 5) initially showed a CBR value below the requirement but was retested and achieved a compliant value of 91.5%. The findings confirm that the planned concrete road pavement corresponds appropriately with the site's soil bearing capacity. Moreover, the study highlights the importance of accurate test point selection to ensure that CBR values are representative of overall conditions. These results are critical for guiding the planning of sustainable and standard-compliant residential road infrastructure.